2023
DOI: 10.1186/s12864-023-09684-9
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping in bambara groundnut [Vigna subterranea (L.) Verdc.] reveals loci associated with agro-morphological traits

Charles U. Uba,
Happiness O. Oselebe,
Abush A. Tesfaye
et al.

Abstract: Background Genome-wide association studies (GWAS) are important for the acceleration of crop improvement through knowledge of marker-trait association (MTA). This report used DArT SNP markers to successfully perform GWAS on agro-morphological traits using 270 bambara groundnut [Vigna subterranea (L.) Verdc.] landraces sourced from diverse origins. The study aimed to identify marker traits association for nine agronomic traits using GWAS and their candidate genes. The experiment was conducted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Additionally, Seo et al [ 73 ] performing GWAS on a collection of 384 Korean cowpea genotypes including landraces, identified four major candidate genes significantly associated with flowering time. Many other GWAS studies in collections that included landraces’ material, revealed candidate genes for phenological and morphological traits in cowpeas and other Vigna species [ 72 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Application Of New Genomic Technologies In Landraces and Ind...mentioning
confidence: 99%
“…Additionally, Seo et al [ 73 ] performing GWAS on a collection of 384 Korean cowpea genotypes including landraces, identified four major candidate genes significantly associated with flowering time. Many other GWAS studies in collections that included landraces’ material, revealed candidate genes for phenological and morphological traits in cowpeas and other Vigna species [ 72 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Application Of New Genomic Technologies In Landraces and Ind...mentioning
confidence: 99%